STUDI PERBANDINGAN BESARAN MEKANIK BETON MENGGUNAKAN PASIR CEPU DENGAN PASIR MUNTILAN - Taufik, Hariyanto (TATAL, 2012)
Concrete is kind of material which have effectiveness to do something, used simple buildingÂ construction or complex building construction. Concrete material is consist of cement as a glue, agregat ofÂ soft sand, rough sand (gravel) and water. Agregat takes 70 â 75 % of concrete volume total.So the quality ofagregat will strong influence to concrete quality. By a good agregat, concrete can be easy done ( workable ),Â strong, durable and economical.Soft agregat (sond ) generally 25 - 65 % agregat total volume. We must beÂ careful to choose sand prosentage to agregat total. Too small sand can produce segrega tie concrete, becauseÂ of more rough agregat. Too much sand which is used can produce low solid. Commonly the sand which isÂ used for mixed for concrete is Muntilan sand, but there is some one who use Cepu sand. From the both ofthe sand after had been tasted produced date of volume mechanic difference (strong pressure, strongÂ pulling, strong curve ) conrete which is used Muntilan sand is higher quality than Cepu sand, but mudÂ prosentage Muntilan sand is higher than mud Cepu sand. It is possibility Muntilan sand rougher than Cepusand or surface of Cepu sand is less sharp. So must do experiment at next time.Keywords : Muntilan sand and Cepu sand, concrete mechanic volume